ANALISIS KESESUAIAN KAWASAN WISATA PANTAI DI PANTAI PALANGPANG, GEOPARK CILETUH-PELABUHANRATU, KABUPATEN SUKABUMI - Yoel Nopriadi Nababan; Qurnia Wulan Sari (Universitas Lambung Mangkurat, 2022)
Beach is one of multidimensional environmental system consisting of natural, socio-cultural interactions, and management systems that located near coastal area. In addition, the natural (or biophysical or ecological) coastal environment system consists of the biota, sediments and water that occur on the coast, their interactions and the ecological and physical processes that shape them. The management system includes many government agencies, non-governmental organizations (NGOs), regulations, policies and programs that interact with each other are highly desirable for harmonious ecological conditions. This multi-dimensional perspective shows that the factors that influence the coastal environment. The aim of this study is to analyze the suitability of tourism at Palangpang Beach Geopark Ciletuh-Pelabuhanratu. The study was conducted from August to September 2021 in the Palanglang Coast Geopark Ciletuh-Pelabuhanratu, Ciwaru Village, Ciemas District, Sukabumi Regency, West Java Province with 3 stations in-situ sampling. The parameters used are water depth, beach type, beach width, water base material, current speed, coastal slope, coastal land cover, hazardous biota, and freshwater availability. The weighting factor assessment was conducted regarding to the coastal tourism suitability index. The Tourism Suitability Index (IKW) of Palangpang Beach at stations 1, 2, and 3 is 85.71%, 92.85%, and 92.85% so it is categorized into very suitable (S1).